Production of bioadsorbent from phosphoric acid pretreated palm kernel shell and coconut shell by two-stage continuous physical activation via N₂ and air - Lee, Chuan Li; H'ng, Paik San; Md Tahir, Paridah; Chin, Kit Ling; Rashid, Umer; Maminski, Mariusz; Go, Wen Ze; Raja Nazrin, Raja Ahmad; Rosli, Siti Nurul Asyikin; Khoo, Pui San (The Royal Society Publishing, 2018)
In the present study, agricultural biomass—palm kernel shell (PKS) and coconut shell (CS)—was used to produce high porosity bioadsorbent using two-stage continuous physical activation method with different gas carrier (air and N2) in each stage. The activation temperature was set constant at 600, 700, 800 or 900°C for both activation stages with the heating rate of 3°C min−1. Two parameters, the gas carrier and activation temperature, were determined as the significant factors on the adsorption properties of bioadsorbent. BET, SEM, FTIR, TGA, CHNS/O and ash content were used to elucidate the developed bioadsorbent prepared from PKS and CS and its capacity towards the adsorption of methylene blue and iodine. The novel process of two-stage continuous physical activation method was able to expose mesopores and micropores that were previously covered/clogged in nature, and simultaneously create new pores. The synthesized bioadsorbents showed that the surface area (PKS: 456.47 m2 g−1, CS: 479.17 m2 g−1), pore size (PKS: 0.63 nm, CS: 0.62 nm) and pore volume (PKS: 0.13 cm3 g−1, CS: 0.15 cm3 g−1) were significantly higher than that of non-treated bioadsorbent. The surface morphology of the raw materials and synthesized bioadsorbent were accessed by SEM. Furthermore, the novel process meets the recent industrial adsorbent requirements such as low activation temperature, high fixed carbon content, high yield, high adsorption properties and high surface area, which are the key factors for large-scale production of bioadsorbent and its usage.